2011
DOI: 10.5539/ijb.v3n3p19
|View full text |Cite
|
Sign up to set email alerts
|

Bioassay Guided Fractionation and Anti-Trypanosomal Effect of Fractions and Crude Aqueous and Methanolic Extracts of Terminalia Avicennioides (Guill. & Perr.) Parts

Abstract: In vitro and in vivo anti-trypanosomal effects as well as reagent-based chemical screening of the aqueous and methanolic extracts of the roots, leaves and stem bark of Terminalia avicennioides were undertaken. In vitro, cessation or drop in the parasite motility, compared to the control, was taken as a measure of the anti-trypanasomal efficacy of the extracts following incubation of the parasite, Trypanosoma brucei brucei, with different extract concentrations (0, 5, 10 and 20 mg/ml) in 96-well micro titre pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…Although not comparable to the effect of the standard drug diminazene aceturate and the plant extract at different concentrations used in this study showed considerable dose dependent antitrypanosomal activity. This finding is in line with earlier reports by [17], [18], [19] and [20] which clearly indicated that plants of different families could possess potent trypanocidal activity.…”
Section: Discussionsupporting
confidence: 93%
“…Although not comparable to the effect of the standard drug diminazene aceturate and the plant extract at different concentrations used in this study showed considerable dose dependent antitrypanosomal activity. This finding is in line with earlier reports by [17], [18], [19] and [20] which clearly indicated that plants of different families could possess potent trypanocidal activity.…”
Section: Discussionsupporting
confidence: 93%
“…However, restlessness and loss of appetite were observed immediately after administration of the extracts, which lasted for 2 hours. The results of this study agree with an earlier report, 21 which recorded no deaths or adverse effects after administering daily oral dose (3000 mg/kg) of the crude methanol extract of A. nilotica to rats for 14 days. However, another study, 22 reported 50% mortality after intraperitoneal administration of 2000 mg/kg of the extract to the experimental animals for 14 days.…”
Section: Acute Toxicity Of Methanol Extract Of Acacia Niloticasupporting
confidence: 92%
“…The significant decrease in PCV of T. brucei brucei infected rats is in consonance with earlier reports [4,25] in trypanosome-infected animals. This has been attributed to the release of hemolytic factors into the animals blood by dead trypanosomes causing destruction of erythrocytes and hence, reduction in PCV [22,26] . It has also been reported that anaemia may be caused by erythrocyte injury caused by lashing action of trypanosome flagella, undulating pyrexia, platelet aggregation, toxins and metabolites from trypanosomes, lipid peroxidation and malnutrition [27] .…”
Section: Discussionmentioning
confidence: 99%
“…A cessation or drop in motility of the parasites in treated blood compared to that of parasite-loaded control blood without extract was taken as a measure of anti-trypanosomal activity, since motility constitutes a relatively reliable indicator of the viability of most zooflagellate parasites [21] . The shorter the time of cessation of motility of the parasite, the more active the extract was considered to be [22] .…”
Section: In Vitro Anti-trypanosomal Screening Of Extracts and Fractiomentioning
confidence: 99%